Extractives of cork (Quercus suber L.): chemical composition of dichloromethane and supercritical CO2 extracts - Castola, Vincent; Marongiu, Bruno; Bighelli, Ange; Floris, Constantino; Laı̈, Adolfo; Casanova, Joseph (Industrial Crops and Products, 2005)
The polymeric matrix of the cork is mainly composed of suberin, lignin and polysaccharides and contains also extractives. Typical components of the extracted mixtures are triterpenes belonging to friedelane, lupane and steroid families and long chain alkanes and alkanols. Two extractive methods have been used, the conventional extraction with a solvent (SE) using dichloromethane (DCM) and the innovative method which uses as solvent supercritical CO2 (SFE) at moderate pressures (200–250 bar). Identiﬁcation and quantitation of the individual triterpenoids and steroids present in the extracts have been carried out by means of the computer aided 13 C NMR analysis without previous separation. Friedelin was found as the main component of the extracts. The main difference between the two extracts concerned the contents of sitost-4-en-3-one which represented 15% of the CO2 extract against 3% in the DCM extract. Similarly, -sitosterol was found in CO2 extract (3%) but not in DCM extract.
Keywords: 13 c nmr; Cork; supercritical extraction; triterpenes

Extractives of cork (Quercus suber L.): chemical composition of dichloromethane and supercritical CO2 extracts (Industrial Crops and Products, 2005)
The polymeric matrix of the cork is mainly composed of suberin, lignin and polysaccharides and contains also extractives. Typical components of the extracted mixtures are triterpenes belonging to friedelane, lupane and steroid families and long chain alkanes and alkanols. Two extractive methods have been used, the conventional extraction with a solvent (SE) using dichloromethane (DCM) and the innovative method which uses as solvent supercritical CO2 (SFE) at moderate pressures (200–250 bar). Identiﬁcation and quantitation of the individual triterpenoids and steroids present in the extracts have been carried out by means of the computer aided 13 C NMR analysis without previous separation. Friedelin was found as the main component of the extracts. The main difference between the two extracts concerned the contents of sitost-4-en-3-one which represented 15% of the CO2 extract against 3% in the DCM extract. Similarly, -sitosterol was found in CO2 extract (3%) but not in DCM extract.